Manager's guide to the Sarbanes-Oxley Act : improving internal controls to prevent fraud - Green, Scott, 1962- (Hoboken, N.J. : Wiley, 2004)
The book introduces the groundbreaking and practical "Control Smart" that not only meets the requirements of Sarbanes-Oxley, but also alerts you if operational controls stop working or are otherwise compromised.
aug 28/05/13
Loans
Includes bibliographical references (p. 219-225) and indexes.
Keywords: Corporations -- Corrupt practices; Disclosure of information -- Law and legislation; Corporations -- Accounting -- Law and legislation; Corporations -- Accounting